Law Protecting Rights: Restoring the law of self-determination in the neo-colonial world - A. Maguire (Law Text Culture, 2008)
In light of the continuing state dominance of international legal relations, it is questionable whether international law adequately protects the right of self-determination. Yet, as it is enshrined in international law, self-determination retains great emancipatory promise. It is therefore essential that the law of self-determination, and its means of implementation, further evolve in order to harness the right’s full potential in the wide range of twenty-first century claims to the right. In this paper I consider self-determination in relation to the contemporary rights claims of Irish nationalists and Indigenous peoples in Australia. This comparison allows for an analysis both of the impacts of colonialism in the present and of the various means by which self-determination may be asserted today. I am advancing two central arguments: firstly, that self-determination retains a mission of decolonisation in the twenty-first century; and secondly, that a ‘human rights approach’ to self-determination presents the best means of advancing the rights of contemporary claimants while protecting the rights of non-claimants.